CDC2-like (CLK) protein kinase inhibition as a novel targeted therapeutic strategy in prostate cancer - Uzor, Simon; Porazinski, Sean R.; Li, Ling; Clark, Bethany; Ajiro, Masahiko; Iida, Kei; Hagiwara, Masatoshi; Alqasem, Abdullah A.; Perks, Claire M.; Wilson, Ian D.; Oltean, Sebastian; Ladomery, Michael R. (Scientific reports, 2021)
Dysregulation of alternative splicing is a feature of cancer, both in aetiology and progression. It occurs because of mutations in splice sites or sites that regulate splicing, or because of the altered expression and activity of splice factors and of splice factor kinases that regulate splice factor activity. Recently the CDC2-like kinases (CLKs) have attracted attention due to their increasing involvement in cancer. We measured the effect of the CLK inhibitor, the benzothiazole TG003, on two prostate cancer cell lines. TG003 reduced cell proliferation and increased apoptosis in PC3 and DU145 cells. Conversely, the overexpression of CLK1 in PC3 cells prevented TG003 from reducing cell proliferation. TG003 slowed scratch closure and reduced cell migration and invasion in a transwell assay. TG003 decisively inhibited the growth of a PC3 cell line xenograft in nude mice. We performed a transcriptomic analysis of cells treated with TG003. We report widespread and consistent changes in alternative splicing of cancer-associated genes including CENPE , ESCO2 , CKAP2 , MELK , ASPH and CD164 in both HeLa and PC3 cells. Together these findings suggest that targeting CLKs will provide novel therapeutic opportunities in prostate cancer.